(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This research work is devoted to the synthesis of a new bis-carbamate N,N’-hexamethylene bis-[(ortho-cresol)-carbamate] i.e. MEE-1 based on diisocyanates and cresols. A possible mechanism of inhibited oxidation for polymers in two stages has been proposed. And also, the brutto (gross) inhibitory activity in model reactions of thermal autoxidation of low-density polyethylene was studied. As a result, it turned out that MEE-1 bis-carbamate increases the thermal-oxidative stability of low-density polyethylene by 2.5-43.2 times compared to other industrial antioxidants and arouses practical interest for further study.